2004
DOI: 10.1002/pi.1677
|View full text |Cite
|
Sign up to set email alerts
|

Particle size and morphology of poly[styrene‐co‐(butyl acrylate)]/nano‐silica composite latex

Abstract: Nanocomposite latex with nano‐silica of varying particle sizes was prepared via in situ polymerization and investigated by submicron particle size analysis, transmission electron microscopy (TEM), scanning electron microscopy (SEM), Fourier‐transform infrared spectrometry (FTIR) and Raman spectrometry. It was found that nanocomposite latex exhibited a core–shell structure with nano‐silica particles enwrapped, resulting in an increase in the latex particle size. The smaller the nano‐silica particles, the more w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Freris et al (12) prepared nano-silica by Stöber method and applied it in the emulsion polymerization to obtain polymer encapsulation of nano-silica particles. However, most literature reported that nanosilica/polyacrylate composite emulsions were synthesized with the available nano-silica or the nano-silica prepared by sol-gel method in ethanol as dispersing media (13,14). These kinds of nano-silica should be redispersed in acrylate before polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Freris et al (12) prepared nano-silica by Stöber method and applied it in the emulsion polymerization to obtain polymer encapsulation of nano-silica particles. However, most literature reported that nanosilica/polyacrylate composite emulsions were synthesized with the available nano-silica or the nano-silica prepared by sol-gel method in ethanol as dispersing media (13,14). These kinds of nano-silica should be redispersed in acrylate before polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the morphological researches of small size silica/polymer composite latex particles prepared via chemical approaches, few composite latex particles with typical core-shell can be found, in which a thin polymer layer should be uniformly grafted or coated on the silica particle surface [12][13][14][15]. Instead, the 'guava-like' [12,13,[16][17][18] and 'raspberry-like' [19][20][21] composite structures are commonly found. This is especially true when the size of silica particles is less than 20 nm [22,23] because a large number of small silica particles would 'accumulate' in the bulk or at the surface of composite latex particles even though silica content is less than 5%.…”
Section: Introductionmentioning
confidence: 99%
“…A number of surface modification methods have been developed to increase the hydrophobicity of IPs . One of the most convenient ways is to cover IPs with a shell of polymer through seeded polymerization, in which the polymer phase and IPs are often linked with coupling agents, for example, silanes with polymerizable double bonds . Fundamental studies on seeded polymerization have been essential to understand the mechanism of controlling the overall morphology of the resultant composite particles.…”
Section: Introductionmentioning
confidence: 99%